Pengembangan Materi Pembelajaran PAI Berbasis Toleransi - Farhan, Farhan; Widodo, Hendro (Al-Ulum: Jurnal Pendidikan Islam, 2023)
This study explains that the main idea of tolerance education lies in how everyone who comes from a different background can then be respected and accepted well so that a peaceful life can be realized in a plural and homogeneous society. To realize this, the authors put forward several principles that are used as the basis, namely: Pancasila as the basis of the state and the 1945 Constitution as well as strengthening the Koran which explains "la ikhraha fi al-din" (there is no compulsion in religion) and the sentence lakum dinukum wa liyadin (for you Your religion and mine is mine. This verse is a strong proof of the Quran's appreciation of religious pluralism, which then requires that every adherent of his religion have a moderate and tolerant.